al-Ādāb al-‘Arabī fī al-‘Aṣr al-‘Abbāsī wa-daur Ibn al-Muqaffa‘ fīhi - Isniyatun Niswah MZ (Program Studi Pendidikan Bahasa Arab, 2023)
The history of the development of knowledge and knowledge of the Arabs cannot be separated from the history of the intersection of Arabs with various civilizations of other nations, both the culture of the Arabs themselves and from other nations. Especially about language and literature. The first Abbasid period was a glorious period in the history of Muslim civilization, especially in Arabic literature, so at that time many literary figures and observers emerged called literati. Many of them who write books, criticize and each other have their own characteristics in their literary works. Unconsciously, the books that come to us and we study today are products produced by ancient thinkers, while we study their works, so we should also know and know them through their life histories and biographies. In this thesis, the author tries to discuss one of the literary figures in the Early Abbasid era and his contribution to the development of Arabic literature, as well as his works that have reached us. He was Ibn al-Muqaffa' whose real name was Rusbah ibn Dzaduwiyah, a Persian descendant who studied Arabic literature. This research is library research with the intention that the data is sourced from written data related to this research. The data collection takes from various library sources, such as: books, theses, articles and various literature that supports research. The approach used is a historical approach with the aim of explaining the development of Arabic literature at that time and the role of Ibn Muqaffa' on the development of literature at that time. Based on the analysis and methods above, it can be seen that Arab scholarship, especially in literature, has developed with the blending of Arab civilization with the Persians